THERMAL RESOURCES AND YIELD OF FORAGE CROPS IN THE CONDITIONS OF KARAKALPAKSTAN - Bekmurat Kh. Turdyshev; Nietbay B. Reimov; Genzhebay U. Saipnazarov; Dauletbay B. Berdikeev (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
With the further development of animal husbandry in the Aral Sea region, the creation of high-quality fodder reserves is still relevant. Since in recent years, large-scale soil salinization of irrigated lands and water shortage, due to the deterioration of the region’s water resources, has led to a reduction in the sown areas of fodder crops and a decrease in their productivity. Along with this, the decrease in the productivity of natural lands, accompanied by a reduction in their species and the alternation of aftermath, does not meet the requirements of animal husbandry in this region [1].